Current concepts in F18 FDG PET/CT-based Radiation Therapy planning for Lung Cancer - Lee, Percy; Kupelian, Patrick; Czernin, Johannes; Ghosh, Partha (Frontiers in Oncology, 2012)
Radiation therapy is an important component of cancer therapy for early stage as well as locally advanced lung cancer. The use of F18 FDG PET/CT has come to the forefront of lung cancer staging and overall treatment decision-making. FDG PET/CT parameters such as standard uptake value and metabolic tumor volume provide important prognostic and predictive information in lung cancer. Importantly, FDG PET/CT for radiation planning has added biological information in defining the gross tumor volume as well as involved nodal disease. For example, accurate target delineation between tumor and atelectasis is facilitated by utilizing PET and CT imaging. Furthermore, there has been meaningful progress in incorporating metabolic information from FDG PET/CT imaging in radiation treatment planning strategies such as radiation dose escalation based on standard uptake value thresholds as well as using respiratory gated PET and CT planning for improved target delineation of moving targets. In addition, PET/CT based follow-up after radiation therapy has provided the possibility of early detection of local as well as distant recurrences after treatment. More research is needed to incorporate other biomarkers such as proliferative and hypoxia biomarkers in PET as well as integrating metabolic information in adaptive, patient-centered, tailored radiation therapy.